Mitigating the Risk of Exploitation and Violence Against Women Indonesian Migrant Workers in The Informal Sector - Berliana Purwono Putri; Heru Sugiyono; Muthia Sakti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to analyze the mitigation of the risk of exploitation and violence against women Indonesian migrant workers in the informal sector as well as the responsibilities of the government and migrant employment agencies. Using the normative juridical method, this research examines relevant legal norms, such as the Indonesian Migrant Workers Protection Act, to evaluate the protection of women migrant workers' rights. Data is obtained from documentation of primary and secondary legal sources, analyzed using a feminist perspective to understand vulnerability factors and challenges in the feminization of migration. The results show that mitigating the risk of exploitation and violence against women Indonesian migrant workers in the informal sector includes preventive measures, such as pre-departure education, skills training, recruitment agency supervision, and legal empowerment. During the working period, protection is carried out through standardized work contracts, access to social protection, and bilateral cooperation, while post-work, economic and social reintegration is carried out through mentoring and entrepreneurship training. However, weak implementation of regulations, lack of oversight, and sectoral silos exacerbate the vulnerability of women Indonesian migrant workers in the informal sector to exploitation, discrimination, and rights violations. The responsibilities of the government and migrant employment agencies include legal protection at all stages of migration, from pre-departure recruitment, monitoring of working conditions, and post-employment reintegration programs to ensure that women migrant workers receive comprehensive protection through effective enforcement of employment contracts, legal aid, monitoring, and social reintegration. This research recommends improved regulation, pre-departure education, recruitment agency supervision, legal empowerment, and post-worker reintegration to reduce the risk of exploitation and violence against women migrant workers.